Gypsum Mud Rheological Behavior - AL-Hashimi, Wissam H. (Journal of Petroleum Research and Studies, 2017)
Gypsum muds are considered as the most important ones used in oil well drilling due to their thermal stability in addition to the durability of their ingredients. The main aim of this work is to study the effect of the gypsum mud compositions on their rheological behavior under the conditions of high-pressure and high temperature. Eleven samples of gypsum mud were tested using Fann viscometer model 50-C. All the tested samples had the same trend of reduction in both plastic viscosity and yield point with increasing temperature. The results showed that with 5 ppb of Q Broxine thermal degradation is obtained at approximately 150 0 F; this is due to the over treatment with thinner which result in more soluble solids and higher rheological properties while the decrement in NaOH concentration from 0.7 ppb to 0.35 ppb results in an increase in both yield point and plastic viscosity; this is due to the loss of OH-1 ions. Six rheological models were adopted: Bingham, power law, modified power law, Robertson stiff, modified Robertson stiff and Casson. Both Robertson stiff model and Casson model showed more acceptable values that fit the experimental data accurately.